Participación Política de los Jóvenes del Cantón Santa Lucía - Cedeño Rodríguez Pedro Alejandro (2024)
Este trabajo investiga la participación política de los jóvenes entre 20 y 24 años en el cantón Santa Lucía. El objetivo principal es analizar los factores socioculturales, económicos y tecnológicos que influyen en sus patrones de participación. Se busca comprender las motivaciones, barreras y facilitadores de su involucramiento en procesos políticos y toma de decisiones. La metodología empleada incluye una encuesta y dos grupos focales. Estas herramientas permitieron determinar los factores que influyen en la participación de los jóvenes lucianos y explorar las diversas percepciones sobre el tema. La encuesta proporcionó datos cuantitativos sobre tendencias y patrones de participación, mientras que los grupos focales ofrecieron una perspectiva más profunda. El estudio aborda cuestiones como el impacto de las redes sociales en la participación política, la influencia de su entorno socioeconómico, y el papel de las tradiciones culturales locales. También se exploran las percepciones de los jóvenes sobre la eficacia de su participación y su confianza en las instituciones políticas. This research investigates the political participation of young individuals aged 20 to 24 in the Santa Lucía canton. The primary objective is to analyze the sociocultural, economic, and technological factors influencing their participation patterns. The study aims to comprehend the motivations, barriers, and facilitators of their involvement in political processes and decision-making.The methodology employed encompasses a survey and two focus groups. These instruments facilitated the determination of factors influencing the participation of young Lucians and enabled the exploration of diverse perceptions on the subject. The survey provided quantitative data on participation trends and patterns, while the focus groups offered a more profound perspective. This study addresses various issues, including the impact of social media on political participation, the influence of socioeconomic environment, and the role of local cultural traditions. Additionally, it explores young people's perceptions regarding the efficacy of their participation and their trust in political institutions. The findings of this research could potentially contribute to the design of strategies aimed at fostering greater youth political engagement in Santa Lucía and provide insights into the complex dynamics of youth political participation in similar contexts.